The impact of dividend tax changes on the performance of Malaysian REITs - Lee, Thean Leong (2015)
This is the first empirical research examining the effects of dividend taxes on the performance of real estate investment trusts (REITs) in Malaysia. The Malaysian government’s announcement of remissions of dividend tax for the REIT sector under the 2007, 2009 and 2011 budgets, provide an excellent but rare opportunity to examine the impact of taxation on stock price performance and stock liquidity. It can be concluded that dividend tax cut announcements made in 2006 and 2008 resulted in a positive stock price reaction from the stock market. The cumulative average abnormal returns (CAARs) are significant at the 10% level across the three event windows. The CAARs for dividend tax remission announced in 2011, on the other hand, are not significantly different from zero. These results support the hypothesis that the announcement of dividend tax reductions increases the wealth of REITs because tax is a form of transaction cost. The insignificance of third announcement CAARs could possible due to lack of new information as it merely extended the dividend tax benefits for another 4 years until 2016. It is also verified that there were no evidence to support the hypothesis that dividend tax cuts will increase the liquidity of REIT shares as proxied by shares trading volume